Innovative methodology for evaluating digital and platform technologies in public finance: will the human factor be under control? - Basiuk , Oleksandr (Pressing Problems of Public Administration, 2024)
The article explores an approach to implementing modern digital technologies, such as blockchain solutions, in the public finance management system, considering global experience. The purpose of the article is to develop recommendations for the implementation of digital technologies into the existing public finance management mechanism of modern Ukraine to reduce objective risks from the “human factor” in corporate and public management, and, in accordance with the goal, 5 research tasks are set and solved in the article. The author analyzes key challenges in public finance management, particularly the negative impact of the human factor, and proposes solutions aimed at minimizing errors, enhancing transparency, and reducing corruption risks. Existing methodologies and frameworks for evaluating digital technologies, such as the digital maturity models of the OECD, the World Bank, ISO 37122, as well as methodologies from NIST and the EU, are examined. The study develops a new methodological approach to the comprehensive evaluation of technologies, encompassing six key criteria: process automation, transparency, security, decentralization, efficiency, and implementation cost. A technology assessment system is proposed for each criterion, along with a mathematical model for calculating an integrated indicator. This methodology enables the classification of technologies as either key or auxiliary in the context of the digital transformation of the public finance management mechanism. The article emphasizes the unique potential of decentralized technologies, such as blockchain, in minimizing the impact of the human factor. The primary contribution of the study lies in creating a scientific basis for enhancing the efficiency of public administration by introducing modern digital technologies capable of minimizing the adverse effects of the human factor. Applying the developed technology evaluation methodology will provide a well-founded means to identify priority areas for the digital transformation of Ukraine’s public finance management system, taking into account global experience and national specifics.